Novel Presentation of Placenta Accreta Spectrum - Sajjad, Rabia; Ashraf, Viqar (Pakistan Armed Forces Medical Journal, 2022)
Placenta accrete spectrum (PAS) previously known as morbid adherent placenta, is a complex obstetric complication that has risen exponentially in the last couple of decades. It carries serious fetomaternal risk in terms of morbidity and mortality, also increasing perinatal mortality owing to prematurity. PAS include three variants depending upon the degree of placental penetration, i.e. accrete, increta and percreta. We highlighted the unique diagnostic criteria of the placenta accrete spectrum,which includes the history of incomplete removal of the placenta, with repeated evacuation, persistent vaginal bleeding and ultrasound evidence of retained products of conception.